নির্বাচিত রাজনৈতিক প্রবন্ধ - বদরুদ্দীন উমর ১৯৩১- (ঢাকা : সুবর্ণ, 2009)
Selected articles on Bangladesh politics since 1971.
গ্রন্থপুঞ্জিগত নির্দেশিকা
In Bengali.
Keywords: Bangladesh -- Politics and government -- 1971-